2021
DOI: 10.2478/dim-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of E-Services and Quality of Life Among Older Consumers in China

Abstract: E-services projects have been successfully implemented and adopted in many countries worldwide. China, one of the developing countries, has also been transitioning itself into this e-services structure. The success of such an effort depends not only on the support of the government but on citizens’ readiness to accept these services, also a central feature. For advanced nations, many studies classify citizens’ acceptance features of e-services, but for emerging countries, such research works are less; for Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…For example, due to the flexibility of time and space, Chen et al (2020) found that the use of e-health can achieve seamless patient care and clinical benefits by investigating the implementation of e-health from the perspectives of stakeholder management in remote locations. Although mobile medical services have a variety of advantages, their development also faces lots of challenges because of their innovativeness as a new application, especially for the elderly users (Zhang et al, 2017;Zhao et al, 2018;Waqas et al, 2021). For one thing, they are not aware of the serious consequences of health problems (Guo et al, 2016).…”
Section: Theoretical Background 21 Mobile Health Services and Protect...mentioning
confidence: 99%
“…For example, due to the flexibility of time and space, Chen et al (2020) found that the use of e-health can achieve seamless patient care and clinical benefits by investigating the implementation of e-health from the perspectives of stakeholder management in remote locations. Although mobile medical services have a variety of advantages, their development also faces lots of challenges because of their innovativeness as a new application, especially for the elderly users (Zhang et al, 2017;Zhao et al, 2018;Waqas et al, 2021). For one thing, they are not aware of the serious consequences of health problems (Guo et al, 2016).…”
Section: Theoretical Background 21 Mobile Health Services and Protect...mentioning
confidence: 99%